EFEK PARAMETER QUALITY PADA KOMPRESI JPEG TERHADAP KUALITAS CITRA DIGITAL DAN RASIO KOMPRESI - helmie Arif Wibawa; Aris Sugiharto (Department of Informatics, Universitas Diponegoro, 2010)
In general, digital image have large amount of file size so that inefficient if wanted to save or transmit it to another place. We require a method to reduce the file. The method which used many is compression. One of them is JPEG compression. At this compression, there is a parameter used to know the quality of compression called quality parameter. So that necessary to check quality parameter effect on JPEG compression to digital images and compression ratio. Keywords : compression, JPEG, quality